Children's Responses to Risk in Agricultural Work in Andhra Pradesh, India - Morrow, V; Vennam, U (Taylor and Francis, 2012)
This paper discusses protection of children from hazards in agricultural work. International and national policies aim to protect children by eliminating all child labour. Previous literature on hazardous child labour tends to focus on single industries or crops, overlooking the variety of activities that children undertake in subsistence farming. We analyse survey and qualitative data from children, and present rates of work, injuries experienced, how children deal with risks, and perceived benefits of work. The most effective form of prevention may be to build on existing knowledge and experience, working with communities to develop strategies to make work safer.